Quo Vadis Penegakan Hukum Bermartabat: Kritik Terhadap Penegakan Hukum Berlandaskan Stigma No Viral No Justice - Muammar, Muammar (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: The emergence of the law enforcement phenomenon based on the stigma of no viral no justice gives a bad image to the face of Indonesian law enforcement, because it leads to a form of law enforcement that is no longer dignified. As a result, the victims must use it in the form of viralizing the case they are experiencing so that they can rally the external power of the public.Purposes of the Research: This paper aims to analyze and examine a number of points that are the basis for law enforcement criticism based on the stigma of no viral no justice.Methods of the Research: This paper uses normative legal research methods. The approaches used are conceptual approaches, theoretical approaches and analytical approaches.Results / Main Findings: Law enforcement based on the stigma of no viral no justice in recent years has tarnished the face of Indonesian law enforcement. In fact, this condition has